Influence of Forward Layered Models for Backcalculation Analysis Based on Falling Weight Deflectometer - Sirithepmontree, Hudsadin; Jitareekul, Poranic; ทรัพย์เสถียร ยโสธร (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
Backcalculation analysis is a commonly used non-destructive testing (NDT) procedure for assessing the in situ material properties of pavements. The accuracy of pavement moduli estimates obtained from FWD backcalculation analysis depends significantly on the forward model employed in the backcalculation process. In order to address this issue, this paper investigates the influence of the forward dynamic model on falling weight deflectometer backcalculation analysis. A dynamic layered model is considered and a corresponding computer code is developed to assess soil system response based on recorded FWD load impulses reported in the literature. This model is applicable to flexible layered pavements. The investigation presented in this study indicates the need for a careful interpretation of the predicted backcalculation moduli which is essential for the development of dynamic backcalculation programs and application in pavement design and construction.